Effect of Sakarya Akgöl Peat on Quality Parameters of Tomato - Nuray Çi̇çek Ati̇kmen; Cihat Kütük (Trakya University Journal of Natural Sciences, 2016)
Tomato is the first ranking plant in greenhouse production both in Turkey and throughout the worldand various media are used for its cultivation. Peat is one of the most preferred media especially for its physical properties. In this study, the potential of Akgöl peat for use as a media for tomato cultivation was analyzed. For this purpose, five different media, including imported moss based peat and Akgöl peat were prepared and they were tested in tomato (Lycopersicon esculentum) cultivation in greenhouse conditions. Testing was conducted as five replicates according to Randomized Block Design. The result showed that there was no significant difference between quality parameters of the fruits except their Vitamin C contents. Total fruit yield and marketable fruit yield pof tomato grown in different media were found to be similar to each other. Tomato plants were successfully grown in all media. Therefore, it was concluded that Akgöl peat can be used as a medium in greenhouse as an alternative to imported moss based peat